Local Government Strategy to Implementing the Economic Pillars of SDGs in the Agro and Marine Areas in Simeulue - Nodi Marefanda; Agatha Debby Reiza Macella; Nellis Mardhiah (Publica: Jurnal Pemikiran Administrasi Negara, 2023)
This research was conducted to find out the local government's strategy in implementing the Economic pillars of SDGs in the agro and marine area of the Simeulue district. Simeulue Regency is one of the agriculture and fisheries-based areas to be precise in the West Teupah and East Simeulue Districts as very strategic locations for superior agro and marine areas to realize SDGs development indicators which have experienced obstacles in achieving them. Farmer groups have achieved very high productivity but marketing is very low and cannot be controlled properly by the government. Likewise, with fishermen groups in the region, the productivity of the fishermen's catches is very large. However, these results are only used by certain groups with marketing prices that do not achieve stability. The research method uses descriptive qualitative. Data analysis was carried out starting from the time of field data collection, data was reduced, presented ,and verified then conclusions were drawn. and the role of BUMDes in advancing superior village products is still weak